Chemically strengthened glass and cover glass
By optimizing the Na/Si intensity ratios in chemically strengthened glass through a two-step ion exchange process, the glass achieves enhanced drop strength, addressing the need for improved impact resistance in cover glasses.
Patent Information
- Application Number
- JP2023097429
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2023-06-14
- Publication Date
- 2024-12-26
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
Cover glasses for mobile devices require further improved strength to withstand impacts and drops from higher positions without breaking.
The distribution of Na in the thickness direction of chemically strengthened glass is optimized to achieve specific Na/Si intensity ratios, enhancing compressive stress and drop strength through a two-step ion exchange process involving Li, Na, and K ions.
The optimized Na profile and Si profile in the glass provide excellent drop strength, ensuring the glass remains intact even when dropped from significant heights.
Smart Images

Figure 2024178979000001
Abstract
Description
[Technical field]
[0001] The present invention relates to chemically strengthened glass. The present invention also relates to a cover glass comprising chemically strengthened glass. [Background technology]
[0002] In recent years, cover glasses have been used for the purpose of protecting and enhancing the aesthetic appearance of display devices such as mobile phones, smartphones, and tablet terminals. The cover glasses used for these applications are required to have excellent strength in order to prevent breakage due to impact or the like.
[0003] Conventionally, a method for increasing the surface strength of glass by immersing the glass in a potassium nitrate molten salt or the like and performing a chemical strengthening treatment has been known. For example, Patent Document 1 discloses that the surface strength of a glass plate is improved by immersing the glass in a potassium nitrate molten salt and performing a chemical strengthening treatment. More specifically, it discloses that the strength of a glass plate is improved by performing a chemical strengthening treatment on a glass containing Li with a molten salt containing Na and a molten salt containing K in that order. It is also disclosed that the mechanism for strengthening the strength of a glass plate by such a chemical treatment is due to compressive stress caused by exchange of alkali metals. [Prior art documents] [Patent documents]
[0004] [Patent Document 1] Patent Publication No. 2022-027424 Summary of the Invention [Problem to be solved by the invention]
[0005] In recent years, there has been a demand for cover glass with even greater strength. The cover glass of a mobile device or the like can break due to deformation when dropped, and so there is a demand for the cover glass to not break even when dropped from a higher height (to have higher drop strength). The present inventors have studied the cover glass described in Patent Document 1 and have found that there is room for improvement in terms of drop strength.
[0006] The present invention has been made in view of the above problems, and an object of the present invention is to provide a chemically strengthened glass having excellent drop strength. Another object of the present invention is to provide a cover glass. [Means for solving the problem]
[0007] As a result of extensive investigation into the above-mentioned problems, the present inventors discovered that higher drop strength can be obtained by making the distribution of Na in the plate thickness direction into a specific state, and thus arrived at the present invention.
[0008] That is, the inventors discovered that the above problems can be solved by the following configuration. [1] A plate-shaped chemically strengthened glass, A chemically strengthened glass, wherein a Na profile and a Si profile in the plate thickness direction of the chemically strengthened glass, which are obtained by analysis with an electron probe microanalyzer, satisfy the relationship of the following formula (I). Formula (I) R Na / Si_100 -R Na / Si_C ≧0.055 In formula (I), R Na / Si_100 is the average value of the Na / Si detection intensity ratio, which is the ratio of the detection intensity of the Na profile to the detection intensity of the Si profile in a range of 91 to 110 μm deep from one surface of the chemically strengthened glass, when the distance in the plate thickness direction of the chemically strengthened glass is defined as the depth. In formula (I), R Na / Si_C is the average value of the Na / Si detection intensity ratio in a range of ±25 μm deep from the center position of the plate thickness of the chemically strengthened glass. [2] The chemically strengthened glass according to [1], further satisfying the following formula (II): Formula (II) R Na / Si_50 -R Na / Si_C ≧0.110 In formula (II), R Na / Si_50 is the average value of the Na / Si detection intensity ratio in the range of 41 to 60 μm deep from the surface. [3] The chemically strengthened glass according to [1] or [2], further satisfying the following formula (III): Formula (III) R Na / Si_100_0 -R Na / Si_C ≧0.155 In formula (III), R Na / Si_100_0 is a value obtained by creating a first regression line in the range of 91 to 110 μm deep from the surface in the profile of the Na / Si detection intensity ratio, and determining the Na / Si detection intensity ratio at the surface position from the first regression line. [4] The chemically strengthened glass according to any one of [1] to [3], wherein a K profile and a Si profile in the plate thickness direction of the chemically strengthened glass, obtained by analysis with an electron probe microanalyzer, satisfy the relationship of the following formula (VI): Formula (VI) R K / Si_2_0 ≦0.310 In formula (VI), R K / Si_2_0 is a value obtained by creating a second regression line in a range of 1 to 3 μm deep from the surface in a profile of a K / Si detection intensity ratio, which is a ratio of the detection intensity of the K profile to the detection intensity of the Si profile, and calculating the K / Si detection intensity ratio at the position of the surface from the second regression line. In formula (VI), R K / Si_C is the average value of the K / Si detection intensity ratio in a range of ±25 μm deep from the center position of the plate thickness of the chemically strengthened glass. [5] The composition at the center of the plate thickness is expressed as a mole percentage based on oxides, SiO 2 55~75% Al 2 O 3 8~20% Li 2O 3 to 15% Na 2 1-5% O K 2 O 0-3% MgO 0-10% Y 2 O 3 0 to 3% ZrO 2 0 to 3% CaO 0-10% SrO 0-5% ZnO 0-5% TiO 2 0 to 3% SnO 2 0 to 1% P 2 O 5 0 to 5% B 2 O 3 Contains 0-10% Y 2 O 3 Content and ZrO 2 ZrO content in total 2 The ratio of the content is 0.0 to 0.7, Y 2 O 3 Content and ZrO 2 The chemically strengthened glass according to any one of [1] to [4], wherein the total content of is more than 0.0% and not more than 3.0%. [6] The composition at the center of the plate thickness is as follows: Na 2 K vs. O content 2 The chemically strengthened glass according to any one of [1] to [5], wherein the ratio of the O content is 0.0 to 1.8. [7] Regarding the composition at the center of the plate thickness, [Al 2 O 3 ]-[Na 2 OK 2 O]+[Li 2 The chemically strengthened glass according to any one of [1] to [6], wherein a value represented by [O] is 15.0 to 26.0. However, [Al 2 O 3 ], [Na 2 OK 2O] and [Li 2 O] are Al 2 O 3 , Na 2 OK 2 O and Li 2 The content of each component of O is expressed as a mole percentage based on the oxide. [8] A plate-shaped chemically strengthened glass, A chemically strengthened glass, wherein a Na profile and a Si profile in the plate thickness direction of the chemically strengthened glass, which are obtained by analysis with an electron probe microanalyzer, satisfy the relationship of the following formula (II): Formula (II) R Na / Si_50 -R Na / Si_C ≧0.110 In formula (II), R Na / Si_50 is the average value of the Na / Si detection intensity ratio, which is the ratio of the detection intensity of the Na profile to the detection intensity of the Si profile in a range of 41 to 60 μm deep from one surface of the chemically strengthened glass, when the distance in the plate thickness direction of the chemically strengthened glass is defined as the depth. In formula (II), R Na / Si_C is the average value of the Na / Si detection intensity ratio in a range of ±25 μm deep from the center position of the plate thickness of the chemically strengthened glass. [9] A plate-shaped chemically strengthened glass, A chemically strengthened glass, wherein a Na profile and a Si profile in the plate thickness direction of the chemically strengthened glass, which are obtained by analysis with an electron beam microanalyzer, satisfy the relationship of the following formula (III): Formula (III) R Na / Si_100_0 -R Na / Si_C ≧0.155 In formula (III), R Na / Si_100_0 is a profile of a Na / Si detection intensity ratio, which is a ratio of the detection intensity of the Na profile to the detection intensity of the Si profile when the distance in the plate thickness direction of the chemically strengthened glass is defined as a depth, and a first regression line is created from a range of 91 to 110 μm deep from the surface in the Na / Si detection intensity ratio profile, and the Na / Si detection intensity ratio at the position of the surface is calculated from the first regression line.
[10] A cover glass comprising the chemically strengthened glass according to any one of [1] to [9]. Effect of the Invention
[0009] According to the present invention, a chemically strengthened glass having excellent drop strength can be provided. The present invention also provides a cover glass. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0010] The chemically strengthened glass of the present invention will be described in detail below, but the present invention is not limited to the following embodiments, and can be arbitrarily modified and implemented within the scope of the present invention. In this specification, the glass composition is expressed in mole percentage based on oxides, and mole % may be simply written as %. In addition, "~" indicating a numerical range is used to mean that the numerical values before and after it are included as the lower and upper limits.
[0011] In the glass composition, "substantially not contained" means that it is not contained except for unavoidable impurities contained in raw materials, etc., that is, it is not intentionally contained. Specifically, the components other than those described as the glass composition are, for example, preferably less than 0.1 mol%, more preferably 0.08 mol% or less, and even more preferably 0.05 mol% or less.
[0012] An optical waveguide surface stress meter can measure the stress of glass accurately in a short time. One example of an optical waveguide surface stress meter is the FSM-6000 manufactured by Orihara Seisakusho. However, in principle, an optical waveguide surface stress meter can only measure stress when the refractive index decreases from the sample surface toward the inside. In chemically strengthened glass, the layer obtained by replacing sodium ions inside the glass with potassium ions from the outside has a refractive index that decreases from the sample surface toward the inside, so the stress can be measured with an optical waveguide surface stress meter. However, the stress of the layer obtained by replacing lithium ions inside the glass with sodium ions from the outside cannot be measured correctly with an optical waveguide surface stress meter.
[0013] The method using a scattered light photoelastic stress meter can measure stress regardless of the refractive index distribution. An example of a scattered light photoelastic stress meter is the SLP1000 manufactured by Orihara Seisakusho Co., Ltd. However, the scattered light photoelastic stress meter is easily affected by surface scattering, and there are cases where the stress near the surface cannot be measured accurately. For the above reasons, accurate stress measurement is possible by combining two types of measuring devices, an optical waveguide surface stress meter and a scattered light photoelastic stress meter.
[0014] The chemically strengthened glass of the present invention includes a first embodiment, a second embodiment, and a third embodiment described later. Each embodiment will be described below.
[0015] <Chemically strengthened glass (first embodiment)> A first embodiment of the chemically strengthened glass of the present invention is a plate-shaped chemically strengthened glass, and the Na profile and Si profile in the plate thickness direction of the chemically strengthened glass obtained by analysis with an electron probe microanalyzer satisfy the relationship of the following formula (I). Formula (I) R Na / Si_100 -R Na / Si_C ≧0.055 In formula (I), R Na / Si_100 is the average value of the ratio of the detection intensity of the Na profile to the detection intensity of the Si profile in a range of 91 to 110 μm deep from one surface of the chemically strengthened glass, where the distance in the plate thickness direction of the chemically strengthened glass is defined as the depth. Hereinafter, the ratio of the detection intensity of the Na profile to the detection intensity of the Si profile will also be simply referred to as the "Na / Si detection intensity ratio." In formula (I), R Na / Si_C is the average value of the Na / Si detection intensity ratio in the range of ±25 μm deep from the center position of the plate thickness of the chemically strengthened glass. A method for detecting and acquiring the Na profile and Si profile, and a method for calculating the Na / Si detection intensity ratio will be described later.
[0016] Satisfying the relationship of the above formula (I) indicates that the detection intensity of Na in a range of 91 to 110 μm deep from one surface of the chemically strengthened glass is relatively higher than the detection intensity of Na in a range of ±25 μm deep from the center position of the sheet thickness. In other words, it indicates that Na is contained in a relatively larger amount in the range of 91 to 110 μm deep from one surface of the chemically strengthened glass than in the range of ±25 μm deep from the center position of the sheet thickness. The mechanism by which the first embodiment of the chemically strengthened glass of the present invention can provide a chemically strengthened glass excellent in drop strength is not necessarily clear, but the present inventors speculate as follows. Chemically strengthened glass such as that of the present invention is often formed by a two-stage chemical strengthening treatment, for example, by replacing Li ions contained in a glass plate with Na ions, and then replacing the Na ions with K ions. In this case, when the chemically strengthened glass satisfies the relationship of the above formula (I), it is considered that Li ions are sufficiently replaced with Na ions in the depth range of 91 to 110 μm. In other words, it is considered that sufficient compressive stress is generated in the depth range, and drop strength is improved.
[0017] Hereinafter, a first embodiment of the chemically strengthened glass of the present invention will be described in detail.
[0018] [Elemental Profile] The above-mentioned Si profile and Na profile are obtained by analysis using an Electron Probe Micro Analyzer (EPMA). In the present invention, the Si profile and Na profile in the sheet thickness direction of the chemically strengthened glass are obtained by the following method. First, the chemically strengthened glass is embedded in a resin, a cross section is prepared on a plane parallel to the plate thickness direction of the chemically strengthened glass, and the cross section is mirror-polished to obtain a measurement sample. The surface of the cross section of the obtained measurement sample of the chemically strengthened glass is analyzed by EPMA. The EPMA analysis is performed using a JEOL JXA-8500F. In the EPMA analysis, a line scan analysis is performed along the thickness direction of the chemically strengthened glass of the measurement sample. The detailed measurement conditions are in accordance with the method described in the following examples. The above measurement provides a Na profile and a Si profile in the sheet thickness direction of the chemically strengthened glass. Note that the above Si profile and Na profile have depth (μm) on the horizontal axis and detection intensity (counts per second: cps) on the vertical axis.
[0019] R in the above formula (I) Na / Si_100 When obtaining the above, first, a profile is created by taking the ratio of the detection intensity of Na to the detection intensity of Si from the obtained Na profile and Si profile. That is, for each measurement point at each depth of each profile, the detection intensity value in the Na profile is divided by the detection intensity value in the Si profile to calculate the value (Na / Si detection intensity ratio), and a profile of the Na / Si detection intensity ratio is created with the horizontal axis representing depth and the vertical axis representing the Na / Si detection intensity ratio. Next, from the profile of the Na / Si detection intensity ratio, the arithmetic average value of the Na / Si detection intensity ratio in the range of 91 to 110 μm deep from one surface of the chemically strengthened glass was calculated, and R Na / Si_100 Let us assume that.
[0020] R in the above formula (I) Na / Si_C is obtained by the following method. From the profile of the Na / Si detection intensity ratio obtained by the above method, the arithmetic average value of the Na / Si detection intensity ratio in the range of ±25 μm depth from the center position of the plate thickness is calculated, and R Na / Si_C Let us assume that. The central position of the plate thickness is determined by measuring the plate thickness from an image observed using a scanning electron microscope attached to the EPMA, and half the depth of that is defined as the central position of the plate thickness. When measuring the plate thickness, the plate thickness is measured at any five points on the observation image, and the arithmetic average of the measurements is defined as the plate thickness.
[0021] [Formula (I)] As described above, the first embodiment of the chemically strengthened glass of the present invention is a plate-shaped chemically strengthened glass, and the Na profile and Si profile in the plate thickness direction of the chemically strengthened glass obtained by EPMA analysis satisfy the following formula (I). Formula (I) R Na / Si_100 -R Na / Si_C ≧0.055 The above formula (I) defines the Na / Si detection intensity ratio in the range of 91 to 110 μm deep from the surface. The magnitude of the value on the left side of the above formula (I) is considered to correspond to the compressive stress in the range of 91 to 110 μm deep from the surface, and is considered to be related to the strength against the stress generated when another object collides with the chemically strengthened glass. If the above formula (I) is satisfied, excellent drop strength can be obtained, but when greater strength against collision is required, it is preferable to adjust the value on the left side of the above formula (I) to be large. For example, in order to increase the strength of chemically strengthened glass against impact, it is preferable for the relationship of the following formula (I-1) to be satisfied, and it is more preferable for the relationship of the following formula (I-2) to be satisfied. Formula (I-1) R Na / Si_100 -R Na / Si_C ≧0.080 Formula (I-2) R Na / Si_100 -R Na / Si_C ≧0.100 Methods for adjusting the parameters of formula (I) are discussed in more detail below.
[0022] [Formula (II)] In the first embodiment of the chemically strengthened glass of the present invention, in addition to the above-mentioned formula (I), the Na profile and Si profile in the sheet thickness direction of the chemically strengthened glass obtained by analysis with EPMA preferably satisfy the relationship of the following formula (II). Formula (II) R Na / Si_50 -R Na / Si_C ≧0.110 In formula (II), R Na / Si_50 is the average value of the Na / Si detection intensity ratio in the range of 41 to 60 μm deep from the surface. In addition, R Na / Si_50is obtained by obtaining a profile of the Na / Si detection intensity ratio by the above-mentioned procedure and calculating the arithmetic mean value of the Na / Si detection intensity ratio in the depth range of 41 to 60 μm. In formula (II), R Na / Si_C is R in the above formula (I). Na / Si_C Since this is the same as the above, the explanation will be omitted.
[0023] The above formula (II) defines the Na / Si detection intensity ratio in the range of 41 to 60 μm deep from the surface. The magnitude of the value on the left side of the above formula (II) is considered to correspond to the compressive stress in the range of 41 to 60 μm deep from the surface, and is considered to be related to the strength against the stress generated when another object collides with the chemically strengthened glass. When greater strength against a collision is required, it is preferable to adjust the value on the left side of the above formula (II) to be larger. For example, in order to increase the strength of chemically strengthened glass against impact, it is preferable for the relationship of the following formula (II-1) to be satisfied, and it is more preferable for the relationship of the following formula (II-2) to be satisfied. Formula (II-1) R Na / Si_50 -R Na / Si_C ≧0.115 Formula (II-2) R Na / Si_50 -R Na / Si_C ≧0.120 Methods for adjusting the parameters of formula (II) are described in detail below.
[0024] [Formula (III)] In the first embodiment of the chemically strengthened glass of the present invention, in addition to the above-mentioned formula (I), the Na profile and Si profile in the sheet thickness direction of the chemically strengthened glass obtained by analysis with EPMA preferably satisfy the relationship of the following formula (III). Formula (III) R Na / Si_100_0 -R Na / Si_C ≧0.155 In formula (III), R Na / Si_100_0 is a value obtained by creating a first regression line in the range of 91 to 110 μm deep from the surface in the profile of the Na / Si detection intensity ratio, and determining the Na / Si detection intensity ratio at the surface position from the first regression line. In formula (III), R Na / Si_C is R in the above formula (I). Na / Si_C Since this is the same as the above, the explanation will be omitted. The Na / Si detection intensity ratio profile is obtained by the procedure described above. The first and second regression lines are created by determining coefficients by the least squares method from the values of each measurement plot of the profile of the Na / Si detection intensity ratio, assuming linear regression. R Na / Si_100_0 corresponds to the Na / Si detection intensity ratio at the surface (depth 0 μm) of the chemically strengthened glass, which is determined by extrapolation from the depth range of 91 to 110 μm.
[0025] The above formula (III) defines a value related to the Na / Si detection intensity ratio in the range of 91 to 110 μm deep from the surface. The magnitude of the value on the left side of the above formula (III) is thought to be related to the compressive stress in the range of 91 to 110 μm deep from the surface, and is thought to be related to the strength against the stress generated when another object collides with the chemically strengthened glass. When greater strength against a collision is required, it is preferable to adjust the value on the left side of the above formula (III) to be larger. For example, in order to increase the strength of chemically strengthened glass against impact, it is preferable for the relationship of the following formula (III-1) to be satisfied, and it is more preferable for the relationship of the following formula (III-2) to be satisfied. Formula (III-1) R Na / Si_100_0 -R Na / Si_C ≧0.160 Formula (III-2) R Na / Si_100_0 -R Na / Si_C ≧0.190 Methods for adjusting the parameters of formula (III) will be described in detail below.
[0026] In the first embodiment of the chemically strengthened glass of the present invention, it is sufficient that the relationship of the above formula (I) is satisfied in a range of 91 to 110 μm deep from one surface of the chemically strengthened glass, but it is preferable that the relationship of the above formula (I) is also satisfied in a range of 91 to 110 μm deep from the other surface. Similarly, with respect to the above formula (II) and the above formula (III), it is preferable that the above-mentioned relationship is satisfied on the one surface and the other surface.
[0027] [Relationship between Na / Si detection intensity ratio] In the first embodiment of the chemically strengthened glass of the present invention, it is also preferable that the Na profile and Si profile in the sheet thickness direction of the chemically strengthened glass obtained by EPMA analysis satisfy the relationship of the following formula (IV). Formula (IV) R Na / Si_50_0 -R Na / Si_C ≧0.140 In formula (IV), R Na / Si_50_0 is a value obtained by creating a first regression line in the range of 41 to 60 μm deep from the surface in the profile of the Na / Si detection intensity ratio, and determining the Na / Si detection intensity ratio at the surface position from the first regression line. In formula (IV), R Na / Si_C is R in the above formula (I). Na / Si_C Since this is the same as the above, the explanation will be omitted. The Na / Si detection intensity ratio profile is obtained by the procedure described above. The first and second regression lines are created by determining coefficients by the least squares method from the values of each measurement plot of the profile of the Na / Si detection intensity ratio, assuming linear regression. R Na / Si_50_0 corresponds to the Na / Si detection intensity ratio on the surface of the chemically strengthened glass, which is obtained by extrapolation from the depth range of 41 to 60 μm.
[0028] The above formula (IV) defines a value related to the Na / Si detection intensity ratio in the range of 41 to 60 μm deep from the surface. The magnitude of the value on the left side of the above formula (IV) is thought to be related to the compressive stress in the range of 41 to 60 μm deep from the surface, and is thought to be related to the strength against the stress generated when another object collides with the chemically strengthened glass. When greater strength against a collision is required, it is preferable to adjust the value on the left side of the above formula (IV) to be larger.
[0029] In the first embodiment of the chemically strengthened glass of the present invention, it is also preferable that the Na profile and Si profile in the sheet thickness direction of the chemically strengthened glass obtained by EPMA analysis satisfy the relationship of the following formula (V). Formula (V) R Na / Si_35 -R Na / Si_C ≧0.125 In formula (V), R Na / Si_35 is the average value of the Na / Si detection intensity ratio in the range of 31 to 40 μm deep from the surface. In addition, R Na / Si_35 is obtained by obtaining a profile of the Na / Si detection intensity ratio by the above-mentioned procedure and calculating the arithmetic mean value of the Na / Si detection intensity ratio in the depth range of 31 to 40 μm. In formula (V), R Na / Si_C is R in the above formula (I). Na / Si_C Since this is the same as the above, the explanation will be omitted.
[0030] [K / Si detection intensity ratio] Moreover, it is preferable that the K profile and Si profile in the sheet thickness direction of the chemically strengthened glass obtained by EPMA analysis satisfy the relationship of the following formula (VI). Formula (VI) R K / Si_2_0 -R K / Si_C ≦0.310 In formula (VI), R K / Si_2_0 is a value obtained by creating a second regression line in a range of 1 to 3 μm deep from the surface in a profile of a K / Si detection intensity ratio, which is a ratio of the detection intensity of the K profile to the detection intensity of the Si profile, and calculating the K / Si detection intensity ratio at the position of the surface from the second regression line. In formula (VI), R K / Si_C is the average value of the K / Si detection intensity ratio in a range of ±25 μm deep from the center position of the plate thickness of the chemically strengthened glass. The method for obtaining the K profile by EPMA is similar to the method for obtaining the Si profile and the Na profile.
[0031] The above formula (VI) defines a value related to the K / Si detection intensity ratio in the range of 1 to 3 μm deep from the surface. The magnitude of the value on the left side of the above formula (VI) is considered to be related to the compressive stress in the range of 1 to 3 μm deep from the surface, and it is considered that the smaller the value on the left side of formula (VI), the smaller the K content in the range of 1 to 3 μm deep from the surface. When the K content is low in the range of 1 to 3 μm deep from the surface, the relationships of the above formulas (II), (III), and (IV), etc., are easily satisfied, and the strength of the chemically strengthened glass against impact is easily increased.
[0032] [composition] A first embodiment of the chemically strengthened glass of the present invention is obtained by subjecting a plate glass before chemical strengthening to a chemical strengthening treatment. A preferred composition of the plate glass before chemical strengthening (hereinafter, simply referred to as "composition before chemical strengthening") will be described below. The composition of the plate glass before chemical strengthening is the same as the composition at the center position of the plate thickness of the chemically strengthened glass.
[0033] The composition before chemical strengthening is expressed as mole percentage based on oxides. SiO 2 55~75% Al 2 O 3 8~20% Li 2 O 3 to 15% Na 2 1-5% O K 2 O 0-3% MgO 0-10% Y 2 O 3 0 to 3% ZrO 2 0 to 3% CaO 0-10% SrO 0-5% ZnO 0-5% TiO 2 0 to 3% SnO 2 0 to 1% P 2 O 5 0 to 5% B2 O 3 Contains 0-10% Y 2 O 3 Content and ZrO 2 ZrO content in total 2 The ratio of the content is 0.0 to 0.7, Y 2 O 3 Content and ZrO 2 The total content of is more than 0.0% and 3.0% or less. The composition before chemical strengthening may be calculated from the amount of each element when the plate glass is produced if the amount is known. The composition before chemical strengthening may be obtained by calculating the content of each element at the center position of the plate thickness of the chemically strengthened glass. The content of each element at the center position of the plate thickness of the chemically strengthened glass can be measured, for example, by EPMA. The content of Li can be measured by glow discharge optical emission spectroscopy. Each component contained in the composition before chemical strengthening will be described below. For example, SiO 2 The oxide-based mole percentage content of SiO 2 ]" may be written as follows.
[0034] SiO 2 is a component that constitutes the network of glass. It also increases chemical durability and reduces the occurrence of cracks when the glass surface is scratched.
[0035] SiO 2 In order to improve chemical durability, the content of SiO is more preferably 60.0% or more, further preferably 62.0% or more, particularly preferably 64.0% or more, and most preferably 66.0% or more. On the other hand, from the viewpoint of improving melting property, SiO 2 The content is more preferably 70.0% or less, further preferably 68.0% or less, particularly preferably 67.0% or less, and most preferably 66.0% or less.
[0036] Al 2 O 3is a component that improves the ion exchange performance during chemical strengthening and increases the surface compressive stress after strengthening. In order to obtain the above effects, Al 2 O 3 The content of Al is more preferably 10.0% or more, and even more preferably, in the following order, 11.0% or more, 11.5% or more, 12.0% or more, 12.5% or more, and 13.0% or more. On the other hand, there are also cases where it is required that crystals are less likely to grow during melting, that devitrification defects are less likely to occur and the yield is more likely to be higher, and that the high-temperature viscosity of the glass is reduced to make it easier to melt. From such a viewpoint, Al 2 O 3 The content is more preferably 15.0% or less, further preferably 14.0% or less, 13.5% or less, and 13.0% or less, in the following order.
[0037] SiO 2 and Al 2 O 3 Both of these are components that stabilize the glass structure. To reduce brittleness, SiO 2 and Al 2 O 3 The total content of is preferably 74.0% or more, more preferably 76.0% or more, and further preferably 78.0% or more. In addition, SiO 2 and Al 2 O 3 Both of these tend to increase the melting temperature of the glass. Therefore, in order to make it easier to melt, SiO 2 and Al 2 O 3 The total content of is preferably 83.0% or less, more preferably 82.0% or less, further preferably 81.0% or less, and particularly preferably 80.5% or less.
[0038] Li 2 O is an ion-exchangeable component and improves the melting property of glass. 2By including O, Li ions on the glass surface are ion-exchanged with external Na ions to be incorporated into the glass, and the incorporated Na ions are then further ion-exchanged with external K ions, which makes it easier to obtain a stress profile with a large surface compressive stress and a thick compressive stress layer. 2 The O content is more preferably 8.0% or more, and further preferably 9.0% or more, 9.5% or more, 10.0% or more, 10.2% or more, and 10.4% or more, in the following order.
[0039] On the other hand, from the viewpoint of reducing the crystal growth rate during glass forming and preventing deterioration of quality due to devitrification, Li 2 The O content is more preferably 14.0% or less, and further preferably 13.5% or less, 13.0% or less, 12.5% or less, 12.0% or less, 11.5% or less, 11.0% or less, and 10.8% or less, in that order.
[0040] Na 2 O and K 2 O is a component that improves the meltability of glass and reduces the crystal growth rate during glass forming. It is also preferable to include a small amount of O in order to improve ion exchange performance.
[0041] Na 2 O is a component that can be ion-exchanged in chemical strengthening treatment using potassium salts, and also a component that reduces the viscosity of glass. 2 The O content is preferably 1% or more, more preferably 1.5% or more, 1.7% or more, 1.9% or more, 2.2% or more, 2.5% or more, 2.8% or more, and 3.0% or more, in the following order. On the other hand, from the viewpoint of avoiding a decrease in the surface compressive stress (Na_CS) in the strengthening treatment with sodium salt, Na 2 The O content is more preferably 4.0% or less, and further preferably 3.0% or less.
[0042] K 2 O is a component that suppresses the rise in devitrification temperature, thereby suppressing devitrification, and also improves ion exchange performance. 2The O content is more preferably 0.1% or more, further preferably 0.15% or more, particularly preferably 0.2% or more, and most preferably 0.5% or more. On the other hand, in order to avoid a decrease in the surface compressive stress (K_CS) during strengthening treatment with sodium salts, K 2 The O content is more preferably 2.5% or less.
[0043] In terms of mole percentage based on oxide, Li 2 O, Na 2 O and K 2 K content relative to total O content 2 Ratio of O content ([K 2 O] / ([Li 2 O]+[Na 2 O]+[K 2 From the viewpoint of improving weather resistance, ([K 2 O] / ([Li 2 O]+[Na 2 O]+[K 2 On the other hand, from the viewpoint of improving the chemical strengthening properties, ([K 2 O] / ([Li 2 O]+[Na 2 O]+[K 2 O])) is preferably 0.20 or less, more preferably 0.18 or less, and even more preferably 0.16 or less.
[0044] From the viewpoint of suppressing the rise in the devitrification temperature and reducing the crystal growth rate, Li 2 O, Na 2 O and K 2 It is preferable that both of the groups [R 2 The sum of the contents of the alkali components represented by [Li 2 O]+[Na 2 O]+[K 2 O]) is preferably 13.0% or more, more preferably 13.5% or more, even more preferably 14.0% or more, particularly preferably 14.5% or more, and most preferably 15.0% or more. From the viewpoint of chemical durability, [R2 O] is preferably 18.0% or less, more preferably 17.5% or less, even more preferably 17.0% or less, particularly preferably 16.5% or less, and most preferably 16.0% or less.
[0045] Also, Na 2 K vs. O content 2 Ratio of O content ([K 2 O] / [Na 2 O]) is preferably 0.0 to 1.8. 2 O] / [Na 2 In order to more easily obtain chemically strengthened glass having excellent drop strength, [K] is preferably 0.3 or more, more preferably 0.5 or more, even more preferably 0.6 or more, and particularly preferably 0.75 or more. 2 O] / [Na 2 From the above viewpoints, the value of [O] is preferably 1.6 or less, more preferably 1.4 or less, and even more preferably 1.2 or less.
[0046] [Al 2 O 3 ]-[Na 2 OK 2 O]+[Li 2 The value represented by [O] is preferably from 15.0 to 26.0, and more preferably from 17.0 to 24.0.
[0047] Y 2 O 3 Y is a component that makes it easier to increase the surface compressive stress of chemically strengthened glass while slowing down the crystal growth rate. 2 O 3 The content of Y is more preferably more than 0%, and further preferably 0.1% or more, 0.2% or more, 0.5% or more, and 1.0% or more, in the following order. On the other hand, Y is preferred because it is easy to increase the compressive stress layer during chemical strengthening treatment. 2 O 3 The content is more preferably 2.0% or less.
[0048] ZrO 2 is a component that makes it easier to increase the surface compressive stress of chemically strengthened glass. 2The content of is more preferably more than 0%, and further preferably 0.1% or more, 0.15% or more, 0.2% or more, 0.25% or more, 0.3% or more, and more than 0.5%, in the following order. On the other hand, ZrO is preferred because it suppresses the occurrence of devitrification defects and makes it easier to increase the compressive stress value during chemical strengthening treatment. 2 The content is more preferably 2.0% or less, further preferably 1.5% or less, particularly preferably 1.0% or less, and most preferably 0.6% or less.
[0049] From the viewpoint of improving the initial solubility, ZrO 2 and Y 2 O 3 The total content of ZrO is more preferably 2.4% or less. 2 and Y 2 O 3 Although there is no particular lower limit for the total content, from the viewpoint of increasing the strength of the glass, the total content is more preferably 0.5% or more, and further preferably 0.7% or more, 1.0% or more, and 1.2% or more, in that order.
[0050] ZrO 2 and Y 2 O 3 ZrO relative to the total content 2 The ratio of the content of [ZrO 2 ] / ([ZrO 2 ]+[Y 2 O 3 ]) is more preferably 0.10 or more, further preferably 0.20 or more, particularly preferably 0.25 or more, and most preferably 0.30 or more. 2 ] / ([ZrO 2 ]+[Y 2 O 3 ]) is more preferably 0.60 or less, further preferably 0.50 or less, particularly preferably 0.45 or less, and most preferably 0.40 or less.
[0051] ZrO 2 and Y 2 O 3 is known as a nucleating agent when added alone, but ZrO 2 and Y2 O 3 By co-adding with ZrO 2 and Y 2 O 3 Since a eutectic is formed, the devitrification temperature, crystal growth rate, and crystallization onset temperature can be controlled. Furthermore, [ZrO 2 ] / ([ZrO 2 ]+[Y 2 O 3 By setting the content of each of the above in the above range, the diffusion of ions in the glass is suppressed, the increase in the devitrification temperature is suppressed, and devitrification can be suppressed. [ZrO 2 ] / ([ZrO 2 ]+[Y 2 O 3 By setting [ZrO 2 ] / ([ZrO 2 ]+[Y 2 O 3 By setting the above range, the temperature range in which nucleation occurs is shifted to the lower temperature side, and the decrease in the crystallization onset temperature is suppressed, thereby improving manufacturing characteristics.
[0052] From the viewpoint of suppressing nucleation, -25×[ZrO 2 ]+100×[Y 2 O 3 -25×[ZrO 2 ]+100×[Y 2 O 3 The lower limit of the value represented by the formula ] is not particularly limited, but ZrO 2 From the viewpoint of suppressing the precipitation of defects in the system, it is preferably 50 or more, more preferably 60 or more, further preferably 70 or more, and particularly preferably 80 or more.
[0053] From the viewpoint of reducing defects in glass, 100×[ZrO 2]+63×[Y 2 O 3 ] is preferably 180 or less, more preferably 175 or less, even more preferably 170 or less, particularly preferably 165 or less, and most preferably 160 or less. 2 ]+63×[Y 2 O 3
[0053] The lower limit of the value represented by
[0053] is not particularly limited, but from the viewpoint of promoting nucleation, it is preferably 100 or more, more preferably 110 or more, even more preferably 125 or more, and particularly preferably 130 or more.
[0054] MgO may be contained to reduce the viscosity during dissolution, etc. The content of MgO is more preferably 0.05% or more, and further preferably 0.1% or more, 0.2% or more, 0.9% or more, more than 0.9%, and 1.0% or more, in the following order. On the other hand, in terms of making it easier to increase the compressive stress layer during chemical strengthening, the MgO content is more preferably 8.0% or less, and even more preferably 7.5% or less, 5.0% or less, 4.0% or less, 3.8% or less, 3.0% or less, 2.0% or less, and 1.5% or less, in that order. By making the MgO content 4.0% or less, acid resistance can be improved.
[0055] Furthermore, by including MgO, the phase transition of the crystal phase from β-quartz solid solution to β-spodumene can be suppressed, and the precipitation of β-spodumene crystals can be suppressed. Therefore, in the second embodiment, it is preferable to include MgO. From the above viewpoint, it is preferable to include MgO in an amount of more than 0.9% and not more than 7.0%. The more preferable range is as described above.
[0056] CaO is a component that improves the melting property of glass and may be contained. The CaO content is more preferably 0.1% or more, even more preferably 0.15% or more, and particularly preferably 0.5% or more. On the other hand, in terms of being easy to increase the compressive stress value during chemical strengthening treatment, the CaO content is more preferably 2.0% or less, even more preferably 1.5% or less, particularly preferably 1.0% or less, and most preferably 0.8% or less.
[0057] In order to increase the stability of the glass, it is more preferable to contain at least one of MgO and CaO, and it is even more preferable to contain MgO. The total content of MgO and CaO is preferably more than 0.1%, more preferably 0.5% or more, and even more preferably 2.0% or more. In terms of further improving the chemical strengthening properties, the total content of MgO and CaO is preferably 20.0% or less, more preferably 15.0% or less, 10.0% or less, and 8.0% or less, in that order.
[0058] SrO is a component that improves the meltability of glass. The content of SrO is more preferably 0.1% or more, further preferably 0.15% or more, and particularly preferably 0.5% or more. In order to facilitate increasing the compressive stress value during chemical strengthening treatment, the SrO content is more preferably 3.0% or less, further preferably 2.0% or less, particularly preferably 1.0% or less, and most preferably 0.5% or less.
[0059] BaO is a component that improves the meltability of glass and may be contained. When BaO is contained, the content is preferably 0.1% or more, more preferably 0.15% or more, and further preferably 0.5% or more. In order to facilitate increasing the compressive stress value during chemical strengthening treatment, the BaO content is preferably 3.0% or less, more preferably 2.0% or less, even more preferably 1.0% or less, and particularly preferably 0.5% or less.
[0060] ZnO is a component that improves the meltability of glass. The ZnO content is more preferably 0.1% or more, further preferably 0.15% or more, and particularly preferably 0.5% or more. In order to facilitate increasing the compressive stress value during chemical strengthening treatment, the ZnO content is more preferably 3.0% or less, even more preferably 2.0% or less, particularly preferably 1.0% or less, and most preferably 0.5% or less.
[0061] lnW is a parameter that represents the degree of oxide mixing, calculated from the contents of alkali metal oxides, alkaline earth metal oxides, and zinc oxide contained in the glass. lnW is expressed by the following formula. lnW=ln(([Li 2 O]+[Na 2 O]+[K 2 O]+[MgO]+[CaO]+[SrO]+[BaO]+[ZnO])! / ([Li 2 O]!×[Na 2 O]!×[K 2 O] × [MgO] × [CaO] × [SrO] × [BaO] × [ZnO] Equation (1) In formula (1), [Li 2 O], [Na 2 OK 2 O, MgO, CaO, SrO, BaO and ZnO are Li 2 O, Na 2 OK 2 The content of each component, O, MgO, CaO, SrO, BaO and ZnO, is expressed as a mole percentage based on the oxide. In addition, ! indicates that a positive number is multiplied by a factorial. For example, [XO]! means that the mole percentage content of the component XO based on the oxide is rounded down to a positive number, and then the positive number is multiplied by a factorial. For example, Na 2 When O is 4.8 mol%, calculate it as the factorial of "4", that is, 4×3×2×1. The larger the value of lnW, the higher the mixing degree of the metal oxides, and the more the devitrification of the glass can be suppressed. From the above viewpoint, lnW is preferably 10 or more, more preferably 12 or more, even more preferably 13 or more, and particularly preferably 14 or more. lnW is preferably 20 or less, more preferably 18 or less, and even more preferably 17 or less.
[0062] La 2 O 3 is not required, but Y 2 O 3 It can be included for the same reasons as La. 2 O 3 is preferably 0.1% or more, more preferably 0.2% or more, further preferably 0.5% or more, and particularly preferably 0.8% or more. On the other hand, if it is too high, it becomes difficult to increase the compressive stress layer during chemical strengthening treatment. 2 O 3 is preferably 5.0% or less, more preferably 3.0% or less, further preferably 2.0% or less, and particularly preferably 1.5% or less.
[0063] TiO 2 is a component that is highly effective in suppressing solarization of glass and may be contained. 2 When contained, the content is preferably 0.02% or more, more preferably 0.03% or more, further preferably 0.04% or more, particularly preferably 0.05% or more, and most preferably 0.06% or more. On the other hand, from the viewpoint of preventing the occurrence of devitrification and the deterioration of the quality of chemically strengthened glass, TiO 2 The content is preferably 1.0% or less, more preferably 0.5% or less, and further preferably 0.25% or less.
[0064] B 2 O 3 B reduces the brittleness of glass and improves the crack resistance, or improves the melting property of glass. 2 O 3 The content is more preferably 0.5% or more, further preferably 1.0% or more, and particularly preferably 2.0% or more. On the other hand, in terms of maintaining good acid resistance, B 2 O 3 The content of is preferably 10% or less. 2 O 3 The content of is more preferably 6.0% or less, further preferably 4.0% or less, and particularly preferably 2.0% or less. From the viewpoint of preventing the occurrence of striae during melting, it is also preferable that the content is substantially zero.
[0065] P 2 O 5 P increases the compressive stress layer during chemical strengthening. 2 O 5 The content is more preferably 0.5% or more, further preferably 1.0% or more, and particularly preferably 2.0% or more. On the other hand, from the viewpoint of increasing acid resistance, P 2 O 5 The content of is more preferably 4.0% or less, and further preferably 2.0% or less. From the viewpoint of preventing the occurrence of striae during melting, it is also preferable that the content is substantially zero.
[0066] Nb 2 O 5、 Ta 2 O 5 , Gd 2 O 3 , CEO 2 is a component that has the effect of suppressing the solarization of glass and improves meltability, and may be contained. When these components are contained, the content of each is preferably 0.03% or more, more preferably 0.1% or more, even more preferably 0.5% or more, particularly preferably 0.8% or more, and most preferably 1.0% or more. On the other hand, it is preferably 3.0% or less, more preferably 2.0% or less, and even more preferably 1.0% or less.
[0067] Fe 2 O 3Since Fe absorbs heat rays, it has the effect of improving the melting property of glass, and is therefore preferable when mass-producing glass using a large melting furnace. In this case, the content is preferably 0.002% or more, more preferably 0.005% or more, even more preferably 0.007% or more, and particularly preferably 0.01% or more, expressed by weight % on the oxide basis. 2 O 3 Since an excessive content of causes coloration, from the viewpoint of enhancing the transparency of the glass, the content thereof, expressed as wt% on an oxide basis, is preferably 0.3% or less, more preferably 0.04% or less, further preferably 0.025% or less, and particularly preferably 0.015% or less.
[0068] Furthermore, other coloring components may be added to the extent that the desired chemical strengthening properties are not hindered. Examples of other coloring components include Co. 3 O 4 , MnO 2 , NiO, CuO, Cr 2 O 3 , V 2 O 5 , Bi 2 O 3 , SeO 2 , Er 2 O 3 , Nd 2 O 3 etc. are preferred.
[0069] SO is used as a fining agent when melting glass. 3 , chloride, fluoride, etc. may be appropriately contained. 2 O 3 It is preferable that Sb is not contained. 2 O 3 When it is contained, it is preferably 0.3% or less, more preferably 0.1% or less, and most preferably not contained. From the viewpoint of fining bubbles in glass, SnO 2 The content of SnO is more preferably 0.1% or more, further preferably 0.2% or more, and particularly preferably 0.3% or more. 2In order to suppress the occurrence of defects, the content is preferably 1% or less, more preferably 0.8% or less, further preferably 0.7% or less, and particularly preferably 0.5% or less.
[0070] (devitrification temperature) The glass before chemical strengthening preferably has a devitrification temperature of 1300° C. or less. The devitrification temperature is more preferably 1280° C. or less, and even more preferably 1250° C. or less. Particularly preferred are 1240° C. or less, 1230° C. or less, 1220° C. or less, and 1210° C. or less, in the following order. The lower limit of the devitrification temperature is not particularly limited, but is usually 1100° C. or more.
[0071] By having a devitrification temperature of 1300°C or lower (preferably 1250°C or lower), the glass can be stably formed, and manufacturing characteristics can be improved. Specifically, for example, when forming glass by the float method, if crystallization occurs before the molten glass is poured into the float bath, the crystals may erode the bricks that make up the float bath. By having a devitrification temperature of 1300°C or lower (preferably 1250°C or lower), erosion of the bricks can be suppressed. The devitrification temperature of glass is the minimum temperature at which no crystals precipitate on the surface or inside of the glass when crushed glass particles of 2 to 3 mm are placed in a platinum dish and heat-treated for 17 hours in an electric furnace controlled at a constant temperature. This temperature is determined by observing the glass with an optical microscope after heat treatment.
[0072] (glass transition temperature Tg, crystallization start temperature Tcs, crystallization peak temperature Tc) In this specification, measurements using a differential scanning calorimeter (DSC) are performed by grinding glass in an agate mortar, obtaining about 70 mg of powder with a uniform particle size of 106 to 180 μm, and heating the powder from room temperature to 1200° C. at a heating rate of 10° C. / min.
[0073] The glass before chemical strengthening has a crystallization start temperature Tcs measured by DSC of preferably 790 ° C. or more, more preferably 800 ° C. or more, even more preferably 810 ° C. or more, even more preferably 815 ° C. or more, particularly preferably 820 ° C. or more, and most preferably 825 ° C. or more. The upper limit of the crystallization start temperature is not particularly limited, but is usually 900 ° C. or less.
[0074] By setting the crystallization onset temperature Tcs to 790°C or higher, the manufacturing characteristics can be improved. Specifically, for example, in molding including a three-dimensional shape in which glass is molded into a plate and then heat-treated (for example, 2.5D or 3D molding. Hereinafter, also referred to as three-dimensional molding), the temperature passes through the nucleation temperature when rising from room temperature to the molding temperature, and defects due to crystallization are likely to occur. By setting the crystallization onset temperature Tcs to 790°C or higher, molding can be performed without passing through the nucleation temperature when rising from room temperature to the molding temperature, and the occurrence of defects can be suppressed.
[0075] A schematic diagram for explaining Tg, Tcs, and Tc in this specification is shown in Figure 1. The glass transition point Tg in this specification is the intersection point of an auxiliary line in a curve obtained by DSC, as shown in Figure 1. The crystallization start temperature Tcs of glass in this specification refers to the temperature of the peak apex when the glass is heated at 10°C / min using DSC.
[0076] The glass before chemical strengthening has a ratio (Tcs+273.15) / (Tg+273.15) of the crystallization start temperature Tcs to the glass transition temperature Tg of 1.10 or more, more preferably 1.15 or more, even more preferably 1.20 or more, and particularly preferably 1.25 or more. By having (Tcs+273.15) / (Tg+273.15) of 1.10 or more, the occurrence of defects in three-dimensional molding can be suppressed and molding characteristics can be improved. The upper limit of (Tcs+273.15) / (Tg+273.15) is not particularly limited, but from the viewpoint of the moldability of the glass, it is usually preferable that it is 1.6 or less. In addition, the units of Tcs and Tg in "(Tcs+273.15) / (Tg+273.15)" are "°C", and "(Tcs+273.15) / (Tg+273.15)" is the same as "Tcs / Tg" when the unit is "K".
[0077] The glass before chemical strengthening has a value (Tcs-Tg) obtained by subtracting the glass transition point Tg from the crystallization onset temperature Tcs of 180°C or more, more preferably 200°C or more. It is further preferably 210°C or more, even more preferably 215°C or more, particularly preferably 225°C or more, and most preferably 230°C or more. By having (Tcs-Tg) of 200°C or more, the occurrence of defects in three-dimensional molding can be suppressed and molding characteristics can be improved. The upper limit of (Tcs-Tg) is not particularly limited, but from the viewpoint of the moldability of glass, it is usually preferably 400°C or less. The glass before chemical strengthening preferably has a value (Tcs-Tg) obtained by subtracting the glass transition point Tg from the crystallization onset temperature Tcs of 180° C. or higher, more preferably 185° C. or higher.
[0078] From the viewpoint of reducing warpage after chemical strengthening, the glass transition temperature Tg is preferably 500° C. or higher, more preferably 520° C. or higher, and even more preferably 540° C. or higher. From the viewpoint of ease of float forming, the glass transition temperature Tg is preferably 750° C. or lower, more preferably 700° C. or lower, even more preferably 650° C. or lower, particularly preferably 600° C. or lower, and most preferably 580° C. or lower.
[0079] The glass before chemical strengthening preferably has a crystallization peak temperature Tc of 790°C or higher, more preferably 800°C or higher, and even more preferably 810°C or higher. The crystallization peak temperature Tc of 790°C or higher allows stable molding. It is most preferable that no crystallization peak is observed. The upper limit of the crystallization peak temperature Tc is not particularly limited, but is usually 950°C or lower.
[0080] (crystal growth rate) By containing MgO in the glass before chemical strengthening, the phase transition from β-quartz solid solution to β-spodumene can be suppressed, and the precipitation of β-spodumene crystals can be suppressed. Therefore, even if the glass before chemical strengthening is held at 1000°C for 30 minutes, the precipitation of β-spodumene can be suppressed. Furthermore, the crystal growth rate can be reduced. When the glass before chemical strengthening contains MgO, only β-quartz solid solution is the first precipitation phase, and the crystal growth rate of the β-quartz solid solution at 1000°C is preferably 4000 μm / hr or less, more preferably 3800 μm / hr or less, even more preferably 3500 μm / hr or less, particularly preferably 3200 μm / hr or less, and most preferably 2700 μm / hr or less.
[0081] In the glass forming process, crystallization in glass can cause defects. For example, when forming glass by the float method, crystallization occurs in the float bath where the temperature range where nucleation occurs overlaps with the temperature range where crystal growth occurs, because the glass is cooled from the high temperature area.
[0082] In normal glasses, the temperature ranges where nucleation occurs and where crystal growth occurs do not overlap, but in Al 2 O 3 and Li 2In glasses containing a large amount of O, the temperature range where nucleation occurs and the temperature range where crystal growth occurs tend to overlap at around 1000°C. Even if the nucleation and crystal growth rates overlap, this is not a defect as long as the crystal growth rate is slow. Therefore, by setting the crystal growth rate of β-quartz solid solution at 1000°C to 600 μm / hr or less, crystallization during the molding process can be suppressed.
[0083] In this specification, the crystal growth rate of β-quartz solid solution at 1000° C. is determined by holding a glass sample at 1000° C. for 30 minutes, measuring the length of the crystals in the glass with a polarizing microscope, and calculating the average value. The crystal growth rate of β-spodumene at 1000° C. is also determined in a similar manner.
[0084] The "β-OH value" is measured by the FT-IR method at a reference wavelength of 4000 cm -1 Transmittance at X 1 (%), the absorption wavelength of the hydroxyl group is 3570 cm -1 Minimum transmittance in the vicinity of X 2 (%) and the thickness t (unit: mm) of the glass plate, using formula (1). β-OH value = (1 / t)log 10 (X 1 / X 2 ) (1) The β-OH value can be adjusted by the amount of water contained in the glass raw materials and the melting conditions.
[0085] Before chemical strengthening, the glass had a β-OH value of 0.1 mm. -1 It is preferable that the thickness is 0.15 mm or more. -1 More preferably, 0.2 mm or more -1 More preferably, 0.22 mm or more -1 More than 0.25 mm is particularly preferable. -1 The above is most preferable.
[0086] The β-OH value is an index of the amount of water in glass. Glass with a large β-OH value tends to have a lower softening point and bend more easily. On the other hand, from the viewpoint of improving strength by chemical strengthening of glass, the larger the β-OH value of glass, the smaller the surface compressive stress (CS) value after chemical strengthening tends to be. From this viewpoint, the β-OH value is set at 0.5 mm -1 Less than 0.4mm is preferable -1 Less than 0.3mm is more preferable. -1 The following is even more preferred:
[0087] In a preferred embodiment described later, when a first stage of chemical strengthening is performed with a Na salt and then a second stage of chemical strengthening is performed with a Li-K mixed salt, K is incorporated into the glass before chemical strengthening, and from the viewpoint that the drop strength of the glass after chemical strengthening is likely to be improved, Na_DOL / K_DOL, which is the ratio of Na_DOL to K_DOL defined below, is preferably 26 or less, and more preferably, in the following order, 25 or less, 24 or less, 23 or less, 22 or less, 21 or less, and 20 or less. Furthermore, from the viewpoint of preventing excessive K from being incorporated into the glass when performing the second stage chemical strengthening with a Li-K mixed salt after the first stage chemical strengthening with a Na salt, thereby preventing breakage of the glass, Na_DOL / K_DOL is preferably 15 or more, and more preferably, in the following order, 16 or more, 16.5 or more, 17 or more, 17.5 or more, and 18 or more. K_DOL: Compressive stress layer depth of chemically strengthened glass ion-exchanged with molten salt consisting of 100% potassium nitrate Na_DOL: Compressive stress layer depth of chemically strengthened glass ion-exchanged with molten salt consisting of 100% sodium nitrate Here, the ion exchange time and temperature used in the calculation of the above K_DOL and Na_DOL are the same conditions.
[0088] Before chemical strengthening, the glass was designed to have a fracture toughness value K1c of 0.800 MPa m in order to improve impact resistance. 1 / 2 It is preferable that the temperature is 0.810 MPa m or more. 1 / 2 More preferably, it is 0.820 MPa m or more.1 / 2 More preferably, it is equal to or greater than 0.830 MPa m 1 / 2 More than 0.840 MPa m, most preferably 0.840 MPa m 1 / 2 The upper limit of the fracture toughness value of the glass of the present invention is not particularly limited, but is typically 1.0 MPa m 1 / 2 The following is the result.
[0089] When the glass before chemical strengthening is a plate-shaped glass plate, the plate thickness (t) is, for example, preferably 2 mm or less, more preferably 1.5 mm or less, even more preferably 1 mm or less, still more preferably 0.9 mm or less, particularly preferably 0.8 mm or less, and most preferably 0.7 mm or less, from the viewpoint of increasing the effect of chemical strengthening. Also, the plate thickness is, for example, preferably 0.4 mm or more, more preferably 0.5 mm or more, from the viewpoint of obtaining a sufficient strength improvement effect by the chemical strengthening treatment.
[0090] The shape of the glass before chemical strengthening may be a shape other than a plate shape depending on the product to which it is applied, its use, etc. The glass plate may also have a border shape with a different thickness around the periphery. The shape of the glass plate is not limited thereto, and for example, the two main surfaces may not be parallel to each other, and one or both of the two main surfaces may be entirely or partially curved. More specifically, the glass plate may be, for example, a flat glass plate without warping, or a curved glass plate having a curved surface.
[0091] (Manufacturing method) The glass before chemical strengthening can be produced by a conventional method. For example, the raw materials of each component of the glass are mixed and heated and melted in a glass melting furnace. The glass is then homogenized by a known method, formed into a desired shape such as a glass plate, and slowly cooled.
[0092] Examples of the glass sheet forming method include the float method, the press method, the fusion method, and the down-draw method. In particular, the float method suitable for mass production is preferred. In addition, continuous forming methods other than the float method, such as the fusion method and the down-draw method, are also preferred.
[0093] Thereafter, the molded glass is ground and polished as necessary to form a glass substrate. When cutting or chamfering the glass substrate into a predetermined shape and size, it is preferable to cut or chamfer the glass substrate before carrying out the chemical strengthening treatment described later, since a compressive stress layer is formed on the end surface by the subsequent chemical strengthening treatment.
[0094] [Chemical strengthening treatment] A first embodiment of the chemically strengthened glass of the present invention is obtained by subjecting a glass plate before chemical strengthening to a chemical strengthening treatment. The chemical strengthening treatment can be performed by a known method. For example, the chemical strengthening treatment is performed by contacting the glass sheet with a molten salt of a metal salt (e.g., potassium nitrate) containing a metal ion with a large ionic radius (typically, K ion). The contact between the glass sheet and the molten salt of the metal salt is performed, for example, by immersing the glass sheet in the molten salt of the metal salt. When the glass sheet comes into contact with the molten metal salt, metal ions with a small ionic radius (typically Na ions or Li ions) in the glass sheet are replaced with metal ions with a large ionic radius (typically K ions for Na ions, and Na ions or K ions for Li ions).
[0095] The chemical strengthening treatment, i.e., ion exchange treatment, can be carried out, for example, by immersing a glass sheet in a molten salt such as potassium nitrate heated to 360 to 600° C. for 0.1 to 500 hours. The heating temperature of the molten salt is preferably 375° C. or higher and 500° C. or lower. The immersion time of the glass sheet in the molten salt is preferably 0.3 hours or higher and 200 hours or shorter.
[0096] Metal salts contained in the molten salt for performing the chemical strengthening treatment include nitrates, sulfates, carbonates, and chlorides. Nitrates include lithium nitrate, sodium nitrate, potassium nitrate, cesium nitrate, and silver nitrate. Sulfates include lithium sulfate, sodium sulfate, potassium sulfate, cesium sulfate, and silver sulfate. Carbonates include lithium carbonate, sodium carbonate, and potassium carbonate. Chlorides include lithium chloride, sodium chloride, potassium chloride, cesium chloride, and silver chloride. These metal salts may be used alone or in combination.
[0097] The parameters in the above formula (I) and the like can be controlled by the treatment conditions of the chemical strengthening treatment. More specifically, the parameters can be adjusted by the type and composition of the molten salt used in the chemical strengthening treatment, the temperature of the molten salt, and the contact time with the molten salt. The parameters can also be adjusted by the composition of the glass before chemical strengthening that is used in the chemical strengthening treatment.
[0098] In this embodiment, the chemical strengthening treatment may be performed only once, or may be performed multiple times under two or more different conditions (multi-stage strengthening). The chemical strengthening treatment may be performed in one stage, but it is preferable to perform the chemical strengthening treatment in two or more stages. In the chemical strengthening treatment, it is preferable to contact the Li-containing glass before chemical strengthening with a molten salt of a metal salt containing at least Na ions (first molten salt), and then with a molten salt of a metal salt containing at least K ions (second molten salt). The first molten salt also preferably contains a metal salt containing Na ions and a metal salt containing K ions. When the first molten salt contains a metal salt containing Na ions and a metal salt containing K ions, the content of the metal salt containing Na ions is preferably 5 mass% or more, more preferably 10 mass% or more, further preferably 20 mass% or more, and particularly preferably 40 mass% or more, based on the total mass of the first molten salt. The first molten salt may also consist only of the metal salt containing Na ions. The second molten salt preferably contains a metal salt containing K ions and a metal salt containing Li ions. The second molten salt may further contain a metal salt containing Na ions.
[0099] In the chemically strengthened glass of the present invention, for example, when the glass thickness is 0.7 mm, the surface compressive stress value is preferably 600 MPa or more, more preferably 700 MPa or more, and even more preferably 800 MPa or more. In the chemically strengthened glass of the present invention, the compressive stress layer depth is usually preferably 60 μm or more, more preferably 70 μm or more, and even more preferably 80 μm or more. When the compressive stress layer depth is 60 μm or more, the drop strength can be further improved.
[0100] <Chemically strengthened glass (second embodiment)> A second embodiment of the chemically strengthened glass of the present invention is a plate-shaped chemically strengthened glass, in which the Na profile and Si profile in the plate thickness direction of the chemically strengthened glass obtained by analysis with an electron probe microanalyzer satisfy the following formula (II). Formula (II) R Na / Si_50 -R Na / Si_C ≧0.110 Since formula (II) is the same as formula (II) explained in the first embodiment, the explanation will be omitted.
[0101] Satisfying the relationship of the above formula (II) indicates that the detection intensity of Na in a range of 41 to 60 μm deep from one surface of the chemically strengthened glass is relatively higher than the detection intensity of Na in a range of ±25 μm deep from the center position of the sheet thickness. In other words, this indicates that Na is contained in a relatively larger amount in a range of 41 to 60 μm deep from one surface of the chemically strengthened glass than in a range of ±25 μm deep from the center position of the sheet thickness. The mechanism by which the second embodiment of the chemically strengthened glass of the present invention can provide a chemically strengthened glass excellent in drop strength is not necessarily clear, but the present inventors speculate as follows. Chemically strengthened glass such as that of the present invention is often formed by a two-stage chemical strengthening treatment, for example, by replacing Li ions contained in a glass plate with Na ions, and then replacing the Na ions with K ions. In this case, when the chemically strengthened glass satisfies the relationship of the above formula (II), it is considered that Li ions are sufficiently replaced with Na ions in the depth range of 41 to 60 μm. In other words, it is considered that sufficient compressive stress is generated in the depth range, and drop strength is improved.
[0102] The second embodiment of the chemically strengthened glass of the present invention is similar to the preferred aspect of the first embodiment except that the relationship of the above formula (II) is satisfied, and therefore description thereof will be omitted. In the second embodiment of the chemically strengthened glass of the present invention, it is also preferable to satisfy the relationship of the above formula (I) described in the first embodiment. It is also preferable to satisfy the relationship of the above formula (I-1) or formula (I-2) described in the first embodiment.
[0103] <Chemically strengthened glass (third embodiment)> A third embodiment of the chemically strengthened glass of the present invention is a plate-shaped chemically strengthened glass, in which the Na profile and Si profile in the plate thickness direction of the chemically strengthened glass obtained by analysis with an electron probe microanalyzer satisfy the following formula (III). Formula (III) R Na / Si_100_0 -R Na / Si_0 ≧0.155 Since formula (III) is the same as formula (III) explained in the first embodiment, the explanation will be omitted.
[0104] Satisfying the relationship of the above formula (III) indicates that the detection intensity of Na in a range of 91 to 110 μm deep from one surface of the chemically strengthened glass is relatively higher than the detection intensity of Na in a range of ±25 μm deep from the center position of the sheet thickness. In other words, this indicates that Na is contained in a relatively larger amount in the range of 91 to 110 μm deep from one surface of the chemically strengthened glass than in the range of ±25 μm deep from the center position of the sheet thickness. The mechanism by which the second embodiment of the chemically strengthened glass of the present invention can provide a chemically strengthened glass excellent in drop strength is not necessarily clear, but the present inventors speculate as follows. Chemically strengthened glass such as that of the present invention is often formed by a two-stage chemical strengthening treatment, for example, by replacing Li ions contained in a glass plate with Na ions, and then replacing the Na ions with K ions. In this case, when the chemically strengthened glass satisfies the relationship of the above formula (III), it is considered that Li ions are sufficiently replaced with Na ions in the depth range of 91 to 110 μm. In other words, it is considered that sufficient compressive stress is generated in the depth range, and drop strength is improved.
[0105] The third embodiment of the chemically strengthened glass of the present invention is similar to the preferred embodiment of the third embodiment except that the relationship of the above formula (III) is satisfied, and therefore description thereof will be omitted. In the third embodiment of the chemically strengthened glass of the present invention, it is also preferable to satisfy the relationship of the above formula (I) described in the first embodiment. It is also preferable to satisfy the relationship of the above formula (I-1) or formula (I-2) described in the first embodiment.
[0106] <Application> The chemically strengthened glass of the present invention (first, second and third embodiments) is useful, for example, as a cover glass. In particular, it is useful as a cover glass for mobile devices such as mobile phones, smartphones, personal digital assistants (PDAs) and tablet terminals. Furthermore, it is also useful as a cover glass for display devices such as televisions (TVs), personal computers (PCs) and touch panels that are not intended to be portable, as building materials such as elevator walls, walls (full-surface displays) of buildings such as houses and buildings, window glass, and table tops, interiors of automobiles and airplanes, etc. It is also useful as a cover glass for the above-mentioned articles. Furthermore, it can be applied to applications such as housings having a curved shape by bending processing and bending forming. EXAMPLES
[0107] The present invention will be described in further detail below with reference to examples. The materials, amounts, ratios, processing contents, processing procedures, etc. shown in the following examples can be changed as appropriate without departing from the spirit of the present invention. Therefore, the scope of the present invention should not be interpreted as being limited by the following examples. Examples 1 to 3 are working examples, and Examples 4 and 5 are comparative examples.
[0108] <Production of chemically strengthened glass> First, glass raw materials were melted in a platinum crucible to prepare glasses so as to obtain each glass composition shown in Table 1, expressed as mole percentages based on oxides. Note that in Table 1 later on, for trace components, the total content of components other than the trace components may be taken as 100 mole percent, and the content may be expressed as a percentage outside the range. Specifically, oxides, hydroxides, carbonates, nitrates, and the like used as glass raw materials were appropriately selected from commonly used glass raw materials and weighed out to give 1000 g of glass. The mixed raw materials were then placed in a platinum crucible and put into a resistance heating electric furnace at 1500-1700°C to melt for about 3 hours, degassed and homogenized to obtain molten glass. The obtained molten glass was poured into a mold material and held at a temperature of glass transition point + 50°C for 1 hour, and then cooled to room temperature at a rate of 0.5°C / min to obtain a glass block. The obtained glass block was cut and ground to obtain a plate glass. Both sides of the obtained plate glass were mirror-finished to finally obtain a plate glass of length 120 mm x width 60 mm x plate thickness 0.7 mm.
[0109] Each of the glass plates obtained by the above procedure was subjected to a chemical strengthening treatment under the conditions shown in Table 1, thereby obtaining chemically strengthened glasses of Examples 1 to 5.
[0110] <Measurement and Evaluation> Measurement samples were prepared using the obtained chemically strengthened glass according to the procedure described above, and analyzed by EPMA (JEOL JXA-8500F) to obtain Na profiles and Si profiles. The measurement conditions for EPMA were as follows: ·Spectroscopic crystal: PETJ (K-Kα), TAPH (Na-Kα), PETH (Si-Kα) Electron beam acceleration voltage: 15kV ·Irradiation electron beam current: 30nA Accumulation time: 1000msec / point ·Measurement point spacing: 1μm
[0111] The drop strength of the chemically strengthened glass of each example was evaluated by the following method. The chemically strengthened glass of each example was fitted into a structure whose mass and rigidity were adjusted to the size of a typical smartphone currently in use, to create a pseudo smartphone. The pseudo smartphone was allowed to fall freely onto #180 SiC sandpaper while changing the height, with the side on which the chemically strengthened glass was placed facing the ground. The drop height was first 5 cm. If the chemically strengthened glass did not break when dropped from a height of 5 cm, it was dropped from a height of 10 cm. Furthermore, if the chemically strengthened glass did not break when dropped from a height of 10 cm, it was dropped from a height of 15 cm. In this way, if the glass did not break when dropped, the operation of dropping it from a position 5 cm higher than the previous drop height was repeated until the chemically strengthened glass broke. The height at which the chemically strengthened glass broke for the first time in the above procedure was taken as the drop height. The drop height was measured for each of the 19 tempered glass sheets, and the arithmetic mean value of the drop heights is shown in the table below as the drop height. In addition, a larger drop height value corresponds to the chemically strengthened glass not breaking even when dropped from a higher position, that is, the glass has a larger drop strength.
[0112] <Result> The composition of the glass before chemical strengthening subjected to the chemical strengthening treatment in each example, the conditions of the chemical strengthening treatment, the above measurement results, and the above evaluation results are shown in the table below. In the table, the "Na / Si profile" column has the following meanings: "31-40μm": the value of the left side of the above formula (V) "41-60 μm": the value of the left side of the above formula (II) "Regression line from 41 to 60 μm": the value of the left side of the above formula (IV) "91-110 μm": the value on the left side of the above formula (I) "Regression line from 91 to 110 μm": the value on the left side of the above formula (III) "Center ±25 μm": R in the above formula (I) Na / Si_C Value of In the table, the "K / Si profile" column has the following meanings: "Regression line of 1-3 μm": the value of the left side of the above formula (VI) "Center ±25 μm": R in the above formula (VI) K / Si_C Value of In the table, the "#180" column in the "Drop strength" column indicates the drop height when dropped onto #180 SiC sandpaper.
[0113] [Table 1]
[0114] From the results shown in Table 1, it was confirmed that Examples 1 to 3, which satisfy the requirements of the above formula (I), i.e., the value in the "91-110 μm" column is 0.055 or more, have superior drop strength to Examples 4 and 5, which do not satisfy the requirements of the above formula (I). Furthermore, from the results shown in Table 1, it was confirmed that Examples 1 to 3, which satisfy the requirements of the above formula (II), i.e., the value in the "41-60 μm" column is 0.110 or more, have superior drop strength to Examples 4 and 5, which do not satisfy the requirements of the above formula (II). From the results shown in Table 1, it was confirmed that Examples 1 to 3, which satisfy the requirements of the above formula (III), i.e., the value in the "91-110 μm regression curve" column is 0.155 or more, have superior drop strength to Examples 4 and 5, which do not satisfy the requirements of the above formula (III).
Claims
1. A plate-shaped chemically strengthened glass, Chemically strengthened glass, wherein the Na profile and Si profile in the thickness direction of the chemically strengthened glass obtained by analysis with an electron probe microanalyzer satisfy the relationship of the following formula (I). Formula (I) R Na/Si_100 -R Na/Si_C ≧0.055 In formula (I), R Na/Si_100 is the ratio of the detection intensity of the Na profile to the detection intensity of the Si profile in a range of 91 to 110 μm from one surface of the chemically strengthened glass, when the distance in the plate thickness direction of the chemically strengthened glass is defined as the depth. It is the average value of the Na / Si detection intensity ratio. In formula (I), R Na/Si_C is the average value of the Na / Si detection intensity ratio in the range of ± 25 μm deep from the center position of the plate thickness of the chemically strengthened glass.
2. The chemically strengthened glass according to claim 1, further satisfying the following formula (II). Formula (II) R Na/Si_50 -R Na/Si_C ≧0.110 In formula (II), R Na/Si_50 is the average value of the Na / Si detection intensity ratio in the range of 41 to 60 μm deep from the surface.
3. The chemically strengthened glass according to claim 1 or 2, further satisfying the following formula (III). Formula (III) R Na/Si_100_0 -R Na/Si_C ≧0.155 In formula (III), R Na/Si_100_0 is a value obtained by creating a first regression line in the range of 91 to 110 μm deep from the surface in the profile of the Na / Si detection intensity ratio, and determining the Na / Si detection intensity ratio at the position of the surface from the first regression line.
4. The chemically strengthened glass according to claim 1 or 2, wherein a K profile and a Si profile in the plate thickness direction of the chemically strengthened glass obtained by analysis with an electron probe microanalyzer satisfy the relationship of the following formula (VI). Formula (VI) R K/Si_2_0 -R K/Si_C ≦0.310 In formula (VI), R K/Si_2_0 is a value obtained by creating a second regression line from a depth range of 1 to 3 μm from the surface in a profile of a K / Si detection intensity ratio, which is a ratio of the detection intensity of the K profile to the detection intensity of the Si profile, and determining the K / Si detection intensity ratio at the position of the surface from the second regression line. In formula (VI), R K/Si_C is the average value of the K / Si detection intensity ratio in the range of ± 25 μm deep from the center position of the plate thickness of the chemically strengthened glass.
5. The composition at the center of the thickness is expressed as a mole percentage based on oxides, SiO 2 55 to 75% Al 2 O 3 を8~20% Li 2 Oを3~15% Na 2 Oを1~5% K 2 O 0 to 3% MgO 0-10% Y 2 O 3 を0~3% ZrO 2 0 to 3% CaO 0-10% SrO 0-5% ZnO 0-5% TiO 2 0 to 3% SnO 2 0 to 1% P 2 O 5 0 to 5% B 2 O 3 Contains 0 to 10% Y 2 O 3 and ZrO 2 ZrO relative to the total content 2 The ratio of the content of is 0.0 to 0.7, Y 2 O 3 and ZrO 2 The chemically strengthened glass according to claim 1 or 2, wherein the total content of is more than 0.0% and 3.0% or less.
6. The composition at the center of the plate thickness is Na 2 K vs. O content 2 The chemically strengthened glass according to claim 1 or 2, wherein the ratio of the O content is 0.0 to 1.
8.
7. Regarding the composition at the center position of the plate thickness, [Al 2 O 3 ]-[Na 2 O]-[K 2 O] + [Li 2 The chemically strengthened glass according to claim 1 or 2, wherein the value represented by [O] is 15.0 to 26.
0. Here, [Al 2 O 3 ], [Na 2 O], [K 2 O] and [Li 2 O] are each Al 2 O 3 , Na 2 O.K. 2 O and Li 2 The content of each of the O components is expressed as a mole percentage based on the oxide.
8. A plate-shaped chemically strengthened glass, Chemically strengthened glass, wherein a Na profile and a Si profile in the plate thickness direction of the chemically strengthened glass obtained by analysis with an electron probe microanalyzer satisfy the relationship of the following formula (II). Formula (II) R Na/Si_50 -R Na/Si_C ≧0.110 In formula (II), R Na/Si_50 is the ratio of the detection intensity of the Na profile to the detection intensity of the Si profile in a range of 41 to 60 μm from one surface of the chemically strengthened glass, when the distance in the plate thickness direction of the chemically strengthened glass is defined as the depth. It is the average value of the Na / Si detection intensity ratio. In formula (II), R Na/Si_C is the average value of the Na / Si detection intensity ratio in the range of ± 25 μm deep from the center position of the plate thickness of the chemically strengthened glass.
9. A plate-shaped chemically strengthened glass, Chemically strengthened glass, wherein the Na profile and Si profile in the plate thickness direction of the chemically strengthened glass obtained by analysis with an electron beam microanalyzer satisfy the relationship of the following formula (III). Formula (III) R Na/Si_100_0 -R Na/Si_C ≧0.155 In formula (III), R Na/Si_100_0 is a profile of a Na / Si detection intensity ratio, which is a ratio of the detection intensity of the Na profile to the detection intensity of the Si profile when the distance in the plate thickness direction of the chemically strengthened glass is defined as the depth. A first regression line is created from a depth range of 91 to 110 μm from the surface, and the Na / Si detection intensity ratio at the position of the surface is calculated from the first regression line.
10. A cover glass comprising the chemically strengthened glass of claim 1 , 2 , 8 or 9 .
Citation Information
Patent Citations
Chemically strengthened glass and method for manufacturing the same
JP2022027424A
